2019
DOI: 10.1021/acs.organomet.8b00778
|View full text |Cite
|
Sign up to set email alerts
|

Optical pKa Control in a Bifunctional Iridium Complex

Abstract: There are few ways to switch a catalyst's reactivity on or off, or change its selectivity, with external radiation; many of these involve photochemical activation of a catalyst. In the case of homogeneous late-transition-metal catalysts, the metal complex itself is frequently the chromophore involved in such reactivity switching. We show here a base-pendant ligand−metal bifunctional scaffold wherein a photobase, a compound that becomes more basic in the excited state (pK a < pK a *), is used to switch the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19] Recent experimental studies performed in the Dawlaty lab have investigated the photochemical properties of a family of 5-R quinoline derivatives. [20][21][22][23][24][25] These compounds were all shown to be photobases, with the magnitude of the photobasicity depending strongly on the identity of the substituent. Specifically, photoexcitation results in Kb increasing by over 10 orders of magnitude when the substituent is the electron-donating NH2 group but only approximately 2 orders of magnitude when the substituent is the electron-withdrawing CN group.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] Recent experimental studies performed in the Dawlaty lab have investigated the photochemical properties of a family of 5-R quinoline derivatives. [20][21][22][23][24][25] These compounds were all shown to be photobases, with the magnitude of the photobasicity depending strongly on the identity of the substituent. Specifically, photoexcitation results in Kb increasing by over 10 orders of magnitude when the substituent is the electron-donating NH2 group but only approximately 2 orders of magnitude when the substituent is the electron-withdrawing CN group.…”
Section: Introductionmentioning
confidence: 99%
“…26 Moreover, two iridium complexes containing pendant quinoline ligands were reported in which the quinoline moiety retained its photobasicity. 27 This represents the first example of a rationally designed transition-metal complex that exhibits photoactivated proton removal functionality.…”
Section: ■ Introductionmentioning
confidence: 95%
“…A series of recent experimental studies by Dawlaty and co-workers focused on the photochemical properties of a family of photobases derived from quinoline. In a series of 5- R -quinolines, they demonstrated that the magnitude of the photobasicity depends strongly on the identity of the substituent, with electron-donating substituents facilitating stronger photobasicity than electron-withdrawing groups. In particular, photoexcitation results in the K b of 5-aminoquinoline increasing by over 10 orders of magnitude whereas the K b of 5-cyanoquinoline only increases by approximately 2 orders of magnitude .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19] Recent experimental studies performed in the Dawlaty lab have investigated the photochemical properties of a family of 5-R quinoline derivatives. [20][21][22][23][24][25] These compounds were all shown to be photobases, with the magnitude of the photobasicity depending strongly on the identity of the substituent. Specifically, photoexcitation results in Kb increasing by over 10 orders of magnitude when the substituent is the electron-donating NH2 group but only approximately 2 orders of magnitude when the substituent is the electron-withdrawing CN group.…”
Section: Introductionmentioning
confidence: 99%